Aureobasidium khasianum (Aureobasidiaceae) a novel species with distinct morphology - Prabhugaonkar, Ashish; Pratibha, J. (Phytotaxa, 2018)
A new species, Aureobasidium khasianum, was found growing on decaying leaves of Wightia speciosissima (Paulowniaceae) in India. It is described here with newly observed morphological features such as formation of setae having adhering conidiogenous cells and producing monilioid conidia. A phylogenetic analysis based on ITS and LSU gene regions is provided to support the taxonomic treatment.